Il colore dell’anguria. «L’ipotesi di una vita diversa» in Autostrada della Cisa di Vittorio Sereni - Maspoli Genetelli, Silvia (L'ospite ingrato, 2025)
The article, which offers a new interpretation of Vittorio Sereni’s poem Autostrada della Cisa, makes use, on the one hand, of multiple intratextual references, which link this poem to other prominent texts by the author (Appuntamento a ora insolita, Pantomima terrestre, Un posto di vacanza, Nell’estate padana, Altro compleanno); on the other hand, it suggests new literary and figurative intertextualities (Frida Kahlo and Diego Rivera), which in turn contribute to shedding light on the poem. The textual analysis, with attention paid to both structural and formal aspects as well as thematic threads (in particular the chromatic one), touches on profound aspects of Sereni’s poetry. Above all, the existential tension between vitality and renunciation.